2009
DOI: 10.2134/jeq2008.0071
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐dependent Extent of Uranium Reduction for Bioremediation of Contaminated Sediment Microcosms

Abstract: Bioremediation of uranium was investigated in microcosm experiments containing contaminated sediments from Oak Ridge, Tennessee to explore the importance of electron donor selection for uranium reduction rate and extent. In these experiments, all of the electron donors, including ethanol, glucose, methanol, and methanol with added humic acids, stimulated the reduction and immobilization of aqueous uranium by the indigenous microbial community. Uranium loss from solution began after the completion of nitrate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…One possible mechanism for uranium reduction in the lactate-amended columns was through organic acid release by Sporomusa, which stimulated uraniumreducing Geobacter, whose presence was supported by the PLFA results. Similar mechanisms have been reported using other electron donors (Edwards et al 2007;Madden et al 2008).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…One possible mechanism for uranium reduction in the lactate-amended columns was through organic acid release by Sporomusa, which stimulated uraniumreducing Geobacter, whose presence was supported by the PLFA results. Similar mechanisms have been reported using other electron donors (Edwards et al 2007;Madden et al 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Luo et al (2007) reported that ethanol resulted in higher uranium reduction than acetate. The extent of U(VI) reduction in Oak Ridge sediments was also found to be higher with methanol than glucose and much higher with glucose as compared to ethanol (Madden et al 2008).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Stimulating indigenous microbial communities to carry out the in situ reduction of soluble U(VI) to insoluble U(IV) has been proposed as a potential bioremediation strategy for these contaminated sites (Anderson et al 2003;Madden et al 2009;N'Guessan et al 2008;Wu et al 2007;Yabusaki et al 2007). However, effective bioremediation requires an understanding of the mechanisms involved in bacterial metal reduction and of the response of microorganisms to metal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, an organic substrate is added to stimulate microbial growth and promote the development of anaerobic conditions, under which the reduction of U(VI) is favored (67). Various substrates (e.g., acetate, ethanol, glucose, and methanol) have been used either in the field or in microcosm studies, and most were capable of stimulating microbial U(VI) reduction (1,8,42,43,47,60); however, the addition of methanol did not always result in U(VI) reduction (49). Many microorganisms are known to reduce U(VI) in pure culture, including a hyperthermophilic archaeon (28), a thermophilic bacterium Thermoterrabacterium ferrireducens (29), the mesophilic dissimilatory metal-reducing bacteria Geobacter and Shewanella (67) and Anaeromyxobacter dehalogenans (71), the sulfate-reducing bacterium Desulfovibrio sp.…”
mentioning
confidence: 99%